A Comparative Clinical Study of Shodhan Uttar Shaman and Shaman Chikitsa in the Management of Amavata with special reference to Rheumatoid Arthritis (AYUSHDHARA, 2023)
The disease Amavata maybe correlated with Rheumatoid Arthritis due to its similar clinical feature. The symptoms of Amavata are Sandhi Shula (pain in joint), Sandhi Sotha (swelling of joints), Sparsahata (tenderness around joint), Angamarda (body ache), Aruchi (anorexia), Trisna (thirst), Gaurava (heaviness) Jvara (fever), Apaka (swelling), Sunnata Anga (loss of sensation). The symptoms of rheumatoid arthritis are morning stiffness, polyarthritis, pitting oedema, proximal muscle stiffness, mimicking with polymyalgia rheumatic swelling of metcarpo-phalangeal joints and proximal interphalangeal joints. Joints are active inflamed if they are tender on pressure and have stress pain on passive movement and soft tissues swelling. So, Amavata may be considered as equivalent to rheumatoid arthritis. The drug selected for management of Amavata (rheumatoid arthritis) were compound formulation normally Amavatari Yoga and Therapy Vaitaran Basti. So, in my study, 60 patients were to be treated in 2 groups. Group- A 30 patients was to be treated with Amavatari Yoga (Lasuna – 1gm + Sunthi – 1gm + Nirgundi – 1gm + Tagar – 1gm) before meal twice daily for 45 days. Group- B 30 patients was to be treated with Vaitaran Basti for 7 consecutive days followed by Amvatari Yoga twice daily for 45 days. The above mentioned Amavatari Yoga and Vaitaran Basti are very effective for the management of Amavata (rheumatoid arthritis) considering their pharmacodynamic action.